Nanocluster impurity gels in superfluid He-II - Mezhov-Deglin, L.P.; Efimov, V.B.; Lokhov, A.V.; Nesvihevsky, V.V.; Dewhurst, C.; Kolmakov, G.V. (Хабаршы. Физика сериясы, 2015)
We discuss here some results of our SANS studies of structure of the impurity-helium condensates, gel samples, prepared by condensation of the gas mixture 4He + 2% of the impurity (D2, O2, vapors of D2O or C2D5OD) on the surface of superfluid He-II cooled below 1.8 K. The impurity nanoclusters covered by a layer of solidified He form the backbone (a dispersive system) of the gel, and liquid helium in the nanopores between the cluster aggregates serves as a dispersion medium.